Investigating the Relationship between Organizational Culture and Quality of Work Life from the Perspective of Nurses Working in the Hospitals of Shahrekord University of Medical Sciences in 2015 - Behnaz Torkan; Sayed Mehdi Razavi Vanani (Golestan University of Medical Sciences, 2017)
Background and objective: Improving quality of work- life ‎ of nurses requires existence of an organizational culture with collaborative and compatible features and with purpose and prospect. Human resources in different organizations such as hospitals with different organizational cultures have different interpretations about quality of work- life ‎; therefore, the aim of this study is to investigate the relationship between organizational culture and quality of work- life ‎ of the nurses  in the hospitals of Shahrekord University of Medical Sciences. Methods: This study was a descriptive-correlation study, which was conducted in 2015 on 295 nurses at the hospitals of Shahrekord University of Medical Sciences. Sampling was performed by using convenience sampling method. Data collection tools were Walton’s quality of work-life questionnaire and Denison’s organizational culture survey. To analyze data, descriptive and analytic statistics methods were used and Spearman correlation coefficient and regression coefficient were also applied.  Results: Results indicated that organizational culture of 76.9% of nurses (227 persons) was mediocre. Also, quality of work life ‎ of 72.92 of nurses was mediocre and only 1.4% enjoyed a good work life and 25/8% had a low level of work life. Results also showed that there is a significant positive correlation between quality of work life ‎ and all components of organizational culture (p<0/05). Also, results of regression analysis showed a positive linear correlation between organizational culture and quality of work- life ‎. Conclusion: Based on the results of this study, improvement in quality of work life ‎ of nurses requires changes in the components of organizational culture and participation of employees in the organization.